2019
DOI: 10.14712/23361964.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effects of mycorrhiza, fulvic acid, seaweed extract and urea on physiological traits and leaf yield of tobacco (Burley 21)

Abstract: To study the effects of mycorrhiza, fulvic acid, seaweed extract and urea on the physiological traits and leaf yield of tobacco, an experiment was carried out in split plots in a randomized complete block design with three replicates at Marivan during 2015. In this study, the main factor was two levels of inoculation with mycorrhiza including: control: no inoculation and inoculation with mycorrhiza (Glomus interaradices) and subplots treated with growth stimulants at 5 kinds: control-distilled water, fulvic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Similarly, in perennial ryegrass the combination of mycorrhizal fungi (R. intraradices) and humic acids spray when applied on the substrate as pre-sowing was more effective in enhancing root biomass and chlorophyll biosynthesis than either products applied alone (Nikbakht et al, 2014). Similar synergistic action between mycorrhiza, sea weed extract and humic acids also has been reported in tobacco (Moradi et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, in perennial ryegrass the combination of mycorrhizal fungi (R. intraradices) and humic acids spray when applied on the substrate as pre-sowing was more effective in enhancing root biomass and chlorophyll biosynthesis than either products applied alone (Nikbakht et al, 2014). Similar synergistic action between mycorrhiza, sea weed extract and humic acids also has been reported in tobacco (Moradi et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…The increased plant height is a response to AMF, which helps in the appropriate absorption of essential nutrients. Furthermore, the inoculation of this fungus to plant roots causes the production of various hormones, such as auxin and gibberellins, and is effective in increasing the plant height and, consequently, the number of leaves [32]. It also improves water and nutrient uptake, photosynthesis potential, and carbohydrate production by altering the root morphology and thereby increasing shoot and root growth.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the generative pattern of mango is more or less similar to cocoa and coffee, the application of those findings could apply to the crops in tropical regions. As indicated earlier, the application of FA improved the growth performances of coffee seedlings (Justi et al, 2019) and also of tobacco (Moradi et al, 2019), whereas in oil palm, the use of FA isolated from palm oil mill effluent as urea coating reduced 50% ammonia volatilization more effective than HA (Rosliza et al, 2009). Moreover, El-Boray et al (2012) reported that the combination of FA application with selected micronutrients (Fe, Za, and Mn) and a consortium of microbes (Serratia sp.…”
Section: Improvement Of Plantation Crop Performances By Famentioning
confidence: 75%
“…FAs have also been studied for their beneficial effect on soils and crops. Some researchers have published their results showing a great potential of FAs as a plant growth stimulator, such as on rice and radish (Khang, 2011), vegetables (Yang et al, 2014), safflower (Moradi et al, 2017), coffee seedlings (Justi et al, 2019), tobacco (Moradi et al, 2019) and wheat (Sootahar et al, 2020). Also, it was reported by Yang et al (2013) that the application of FAs on soils significantly improved soil-P availability.…”
Section: Introductionmentioning
confidence: 99%